A critical analysis of mainstreaming youth volunteering in environmental governance of Pakistan: a multi-level approach - Gul, Mohsen (2021)
The overall aim of the study was to critically analyse how volunteerism as a mode of youth engagement in environmental governance in Pakistan was shaped by geographical contexts, policy and governance frameworks, and volunteer engagement practices at multiple governance levels (international, national, provincial, and local levels). There were many ways this analysis could have been approached. I chose to use the concept of multiple environmentalities inspired by Michel Foucault's writings on techniques and rationalities involved in both governing the self and governing others. I used the critical lens of identifying both complementing and conflicting environmentalities (sovereign, disciplinary, neo-liberal, according to truth and communal) coming together to form un-interrogated assumptions, taken-for-granted truths, rationales, and technologies that, in diffuse and complex ways, control mainstreaming of youth volunteerism in environmental governance structures across multiple geographical levels. The research design was inductive in nature and a grounded theory approach was used to critically analyse multi-level environmental governance and the role of young environmental volunteers in it across different geographical levels. A theoretical sampling method was used to select case study organisations and policy participants at each geographical level. An ethnographic strategy was employed in using a variety of qualitative data collection tools including participant observation, semi-structured interviews and focus group discussions, along with document analysis and photo elicitation. In this thesis, I have highlighted the complex and constructed nature of environmental volunteering perceived and experienced by young people across different geographical levels. I have argued that youth volunteering in Pakistan is not a fixed, unproblematic object but a phenomenon whose boundaries have been continuously managed and utilised by various actors (state and non-state). I constructed a brief genealogy of youth and environmental volunteering in Pakistan and their relationship to broader socio-economic discourses to better understand how these phenomena came to be produced in the contemporary period. Across the historical account, a multitude of complementing and contesting reasons and methods were identified which were employed by the state, non-state actors and young people themselves to take up volunteering or action for the environment. I argued that the relationship between youth and volunteering cannot be considered positive and unequivocal by default as multiple factors, historical and current, come into play when forming this habitus. Several study respondents highlighted that both, state and non-state actors, struggled to define and bring together concepts of youth volunteering and environment, which led to their limited interest in developing formal environmental volunteering channels for young people across the national and sub-national levels. In addition to environmental value orientations and concerns, young people identified altruistic, egoistic, and hedonic values they associate with volunteering and how they come together to form environmental volunteering rationalities for them. I also discussed the technologies of power, resistance and self-transformation employed to undertake youth environmental volunteering across different geographical levels. While some generalisations can be drawn, it is essential to appreciate the non-fixity of these power relations, available technologies, and their experience by one or many actors involved. The social class difference appeared to manifest in young people’s experiences of volunteering across all geographical levels. Through capturing the lived experiences of young environmental volunteers, I showed that they were constantly forming their own environmental identities by engaging with state and non-state technologies and through their own technologies of self-transformation. The research also showcased that gaining access to environmental volunteering spaces and activities was a highly gendered experience, often exacerbating existing gender inequalities at different geographical levels. Besides the challenges, it also showed that young female volunteers were claiming more spaces of environmental action and destabilising gender norms through their voice and action. I acknowledged that there was a lack of understanding about how young people experience volunteering through the combination of the identified rationales and technologies of power, resistance, and self-transformation, all simultaneously diffused and emanating from multiple sites or in a field of ordering forces. Finally, I presented a framework model outlining barriers and facilitators for using youth volunteering as a mode of environmental governance at multiple geographical levels.